Text mining approaches for analyzing an Indonesian tafseer and translation of the holy Quran - Ayu, Media Anugerah; Irawan, Edi; Mantoro, Teddy (Institute of Advanced Engineering and Science, 2022)
The Indonesian tafseer and translation of Holy Quran is an important source of information and knowledge for Indonesian muslims, since not many Indonesian muslims understand Arabic language in the Quran. However, the tafseer is full of the commentaries and explanation of each surah (chapter) and/or ayah (verse), which form a large document and not so easy to be accessed. Thus, the challenge is how to refer to both tafseer and translation in faster and accurate ways as one needs to always refer to them back and forth. Hence, this study proposes several text mining approaches, i.e. most frequent words, K-means clustering, and association rules, to analyze an Indonesian tafseer and translation of Quran and provide insights of hidden knowledge and relationships based on statistical information derived from it. These insights could be useful for muslims in general and for people that doing research in related areas. This study shows interesting results from combined analysis of the approaches used which can help people accessing information in tafseer more efficiently. As well, interesting relationships have been drawn from terms in the tafseer which could provide further and deeper knowledge on messages in the Quran.